2022
DOI: 10.1097/mol.0000000000000844
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cardiovascular calcification by lipids and lipoproteins

Abstract: Purpose of reviewLipids and lipoproteins have long been known to contribute to atherosclerosis and cardiovascular calcification. One theme of recent work is the study of lipoprotein (a) [Lp(a)], a lipoprotein particle similar to LDL-cholesterol that carries a long apoprotein tail and most of the circulating oxidized phospholipids.Recent findingsIn-vitro studies show that Lp(a) stimulates osteoblastic differentiation and mineralization of vascular smooth muscle cells, while the association of Lp(a) with coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…With the in-depth study of lipid metabolism, it is found that lipid metabolism not only plays a key role in the occurrence and development of cardiovascular diseases, metabolic syndrome and other chronic diseases 11 , but also has a signi cant impact on the occurrence and development of malignant tumors 12 .…”
Section: Discussionmentioning
confidence: 99%
“…With the in-depth study of lipid metabolism, it is found that lipid metabolism not only plays a key role in the occurrence and development of cardiovascular diseases, metabolic syndrome and other chronic diseases 11 , but also has a signi cant impact on the occurrence and development of malignant tumors 12 .…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 25 However, accumulating evidence suggests that hyperlipidemia and inflammation are actively involved in the pathogenesis of coronary calcification. 30 , 31 Previous studies show that ox-LDL and lp(a) could induce osteoblastic differentiation and mineralization of vascular smooth muscle cells by upregulating expressions of BMP-2, 32 while proinflammatory cytokines (eg, tumor necrosis factor α [TNF-α], interleukin 6 [IL-6], and IL-1β) actively involved in atherosclerosis can also promote matrix mineralization in extraosseous cells. 30 Histological studies show that coronary calcifications usually colocalize with apoptotic macrophages, cholesterol crystals, and large necrotic core within advanced coronary plaques, 1 suggesting that calcifications might be an indicator for unresolved inflammation within the coronary plaques, while associations between RvD1 and culprit plaque calcification could be secondary to chronic local arterial inflammation.…”
Section: Discussionmentioning
confidence: 99%